Pest categorisation of Toxoptera citricida. (11th January 2018) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; Navarro, Maria Navajas; Niere, Björn; et al.
Abstract: The European Commission requested EFSA to conduct a pest categorisation of Toxoptera citricida (Hemiptera: Aphididae), an oligophagous aphid developing and reproducing parthenogenetically on tender leaf and flower flush of citrus (Rutaceae). T. citricida is a taxonomic entity with reliable methods available for detection and identification. It is regulated in the EU by Council Directive 2000/29/EC where it is listed in Annex IIAI as a harmful organism whose introduction and spread into the EU shall be banned. T. citricida is native to tropical regions of Southeast Asia and has spread to most citrus‐growing areas worldwide, except California and the Mediterranean basin, causing significant damage to citrus as it is the most efficient vector of the Citrus tristeza virus (CTV). T. citricida occurs in Madeira and, with a restricted distribution, in the north‐west of the Iberian Peninsula, mostly on backyard citrus trees. This may have hindered the effectiveness of the official control measures in these areas. There are further phytosanitary measures in place in the EU in order to limit entry via traded commodities. Citrus plants for planting are regulated and are a closed pathway. However, there is uncertainty regarding host status of some non‐rutaceous plants on which this aphid has been recorded and so other plant genera may provide additional pathways. The EFSA Plant Health Panel concludes that the establishment of T. citricida in the main EU citrus growing areas around the Mediterranean would have significant impacts because of its ability to vector CTV. Considering the criteria within the remit of EFSA to assess the status as a potential Union quarantine pest (QP), as a potential protected zone quarantine pest (PZQP) or as a potential regulated non‐quarantine pest (RNQP), T. citricida meets with no uncertainties the criteria assessed by EFSA for consideration as a potential Union QP.